World Development Report 2015 : Mind, Society, and Behavior - World Bank Group (Washington, DC: World Bank, 2014)
Every policy relies on explicit or implicit assumptions about how people make choices. Those assumptions typically rest on an idealized model of how people think, rather than an understanding of how everyday thinking actually works. This year’s World Development Report argues that a more realistic account of decision-making and behavior will make development policy more effective.